MRI of the Prostate With and Without Endorectal Coil at 3 T: Correlation With Whole-Mount Histopathologic Gleason Score - Dhatt, Ravjot; Choy, Stephen; Co, Steven J; Ischia, Joseph; Kozlowski, Piotr; Harris, Alison C; Jones, Edward C; Black, Peter C; Goldenberg, S Larry; Chang, Silvia D (American journal of roentgenology (1976), 2020)
The purpose of this article is to prospectively compare image quality and diagnostic accuracy of clinically significant prostate cancer with and without endorectal coil (ERC) at 3 T using a combination of T2-weighted and diffusion-weighted MRI. Twenty-three patients with biopsy-proven prostate cancer underwent MRI with and without ERC at the same visit. Patients subsequently underwent radical prostatectomy. Specimens were assessed by whole-mount histopathologic examination. Two radiologists reviewed MR images for image quality (5-point scale) and disease using Prostate Imaging Reporting and Data Systems version 2 (PI-RADSv2). Sensitivity, specificity, and area under the receiver-operator curve (AUC) were calculated with and without ERC. Additionally, apparent diffusion coefficient (ADC) was correlated with Gleason score and ADC values of each lesion were compared with and without ERC. Image quality was comparable with and without ERC (3.8 vs 3.5). Twenty-nine cancer foci larger than 0.5 cm in diameter were found in 23 patients on histopathologic examination; 18 tumors had a Gleason score of 7 or greater. Two radiologists recorded AUC for tumors with a Gleason score of 7 or greater as 0.96 and 0.96 with ERC and 0.88 and 0.91 without ERC. All 13 tumors with a Gleason score of 3 + 4 were detected with ERC, but only 9 were detected without ERC. One of five tumors with Gleason scores less than 3 + 4 was missed with and without ERC. ADC significantly correlated with Gleason score. There was no significant difference in the ADC of a lesion on MRI with and without an ERC. MRI with and without ERC was equally accurate at showing prostate cancers with Gleason scores of 4 + 3 or greater. However, MRI with ERC was superior at showing cancer with a Gleason score of 3 + 4. There was no significant difference in ADC values between scores acquired with or without an ERC.